Jewish Palestinian Aramaic: Chronology, Geography, and Typology - Fassberg, Steven E. (Aramaic studies, 2021)
Abstract Jewish Palestinian Aramaic was the language of the Jews of Palestine and is identifiable from around the third or fourth centuries CE until the last centuries of the first millennium, by which time it was completely displaced in speech by Arabic. This article surveys its origins and subsequent stages of development, chronologically from Palestinian Targumic to Palestinian Talmudic to Late Jewish Literary Aramaic. Geonic and post-Geonic scribes were not kind to manuscripts written in Jewish Palestinian Aramaic since they did not know the language and were influenced by the more prestigious Babylonian Aramaic. As a result, they sometimes inserted Aramaic forms they knew from non-Palestinian texts. It is probably these scribes who are responsible for the ‘ gemischtem Sprachtypus ’ of the late targumim.